Application of Fatwa DSN MUI Number 144 concerning Sharia Marketplace on the Shopee Application - Miftahul Ikhsan, Muhammad; Meiriyanti, Deffa (Zona Law And Public Administration Indonesia, 2024)
technology as part of our lives today. The life that was originally a lot of activities and socializing turned into a digital world. Now the marketplace is one of the commodity giants in buying and selling. Shopee is ranked first as a forum for sellers and buyers. There are so many features that can be used in one transaction, both from the payment system, the retrieval system. This type of research uses literature research that takes data through information by obtaining library materials, data techniques that have been obtained by reviewing and analyzing, both in the form of books, journals, research results. As well as by using descriptive analysis techniques. . researchers concluded that shopee marketplace whether to implement DSN MUI fatwa number 144 about sharia marketplaces became the author's consensual, namely there were four that have not been implemented by the fatwa, the first of which was the sale and purchase of liquor, besides that there was buying and selling pork, both pork crackers, sausages, and pork, thirdly there were loans containing usury, namely shopee paylater, Finally, there are cases related to shipping services and Shopee does not want to be responsible for damage and loss of consumer goods